(3TQM GdOQI GdHjVGA aj GdaQGFV ddCNVQjs - (3eLghds ((3SYjO Hf GMeO CHh YQhS Hf CMeO efUhQs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdehUha HUaI GdYXeI hGdceGd hHYO aEfj deG QCjJ GdJCdja GdeSei HGdOQI GdHjVGA GdPj Cdag GdCNVQj SeM dj Cf CTQM TQMG jMd CdaGXgs
(3BNQgG (B:s
(3hbhd ef GdeOjf eJYdb jbHVhG hbhdg eYGdge eJYdb HMce hGddg CYde Ke bGd hgPg fgGjI GdeQGO EdN GdfXe JUhQ LejYI XGgQIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc (B: (3eMeO CHh GdSYGOGJ fLd GdSjO MSf Sdje eaJj jGaG GdOLGfj SfI (B1317 (3g`s
Keywords: (3GdaQGFVs